Recovery of phosphate, magnesium and ammonium from eutrophic water by struvite biomineralization through free and immobilized Bacillus cereus MRR2. (20th October 2021) - Han, Zuozhen; Guo, Na; Yan, Huaxiao; Xu, Yudong; Wang, Jihan; Zhao, Yanyang; Zhao, Yanhong; Meng, Long; Chi, Xiangqun; Zhao, Hui; Tucker, Maurice E.
Abstract: Treating eutrophic water by struvite biomineralization has been studied for many years due to its much lower costs than physicochemical methods. In this study, an eco-friendly method applying biological processes to precipitate phosphate, magnesium and ammonium ions as struvite using free and immobilized Bacillus cereus MRR2 bacteria was studied. The results showed that the higher alkalinity and supersaturation derived from alkaline phosphatase and ammonia released by the bacteria facilitated struvite nucleation. The biogenesis of coffin-like and tetragonal-pyramid-shaped struvite was proved by the presence of diversified organic functional groups and secondary protein structures, as well as different C1S and S2p peaks through XRD, Rietveld refinement, SEM-EDS, FTIR and XPS analyses. STEM and element mapping results showed that the ammonium, phosphate and magnesium ions had diffused from the outside to the inside of the cell. The optimal immobilization conditions of Bacillus cereus MRR2 were obtained by a response surface methodology (12.3% bacteria amount, 8.3% activated carbon, 0.3% polyvinyl alcohol, 2% sodium alginate, 4% calcium chloride, 3% boric acid solution and 24 h cross-linking time). The removal ratio of phosphate, magnesium and ammonium ions by immobilized bacteria in 15 days reached 90.1%, 95.6% and 95.7%, respectively, much higher than the 73.3%, 83.8% and 89.1% values using free bacteria. The application of immobilized Bacillus cereus MRR2 will provide a simple eco-friendly and economic method for simultaneous removal of phosphate, magnesium and ammonium ions and also for continuous struvite recovery, which can supply a reference for the treatment of eutrophic water. Graphical abstract: Image 1 Highlights: Alkaline phosphatase and ammonia together resulted in pH increase up to 9.0. Struvite could be recycled in eutrophic water treatment by Bacillus cereus. The optimal immobilization condition of Bacillus cereus strain was further studied. Phosphate and ammonium decreased by 90.1% and 95.7% by immobilized bacteria. Treating eutrophic water by immobilized bacteria can obtain higher economic profit.